The Failed Jewish Reform at the Time of Antiochus IV. and Paul’s Missionary Strategy - Gaß, Erasmus (Biblische Zeitschrift, 2020)
The reform at the time of Antiochus IV. Epiphanes was a serious intervention in the religious system of the Jews. Though being judged as anachronistic and archaic from the outside, the Jewish identity markers could not be given up at that time since they were theologically loaded. Paul and the emerging Christian communities took over the Seleucid-Maccabean challenge and sustainably reformed the Jewish identity markers. Circumcision was good for Jews, but irrelevant for Gentile believers. The abomination of swine was no longer useful since purity had to be understood in an ethical sense. Last but not least, the Sabbath commandment was accepted because this rule was explained by creation theology and, thus, had social implications. The requirements of the failed reform at the time of Antiochus worked about 200 years later, in a different context (Syria) and in an eschatological setting (imminent parousia).